2015
DOI: 10.1038/nchembio.1961
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acid catabolism fuels adipocyte differentiation and lipogenesis

Abstract: Adipose tissue plays important roles in regulating carbohydrate and lipid homeostasis, though less is known about the regulation of amino acid metabolism in adipocytes. Here we applied isotope tracing to pre–adipocytes and differentiated adipocytes to quantify the contributions of different substrates to tricarboxylic acid metabolism and lipogenesis. In contrast to proliferating cells that use glucose and glutamine for acetyl–coenzyme A (AcCoA) generation, differentiated adipocytes increased branched chain ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
342
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(364 citation statements)
references
References 50 publications
16
342
4
2
Order By: Relevance
“…S2, G–I). This is consistent with recent work demonstrating minimal catabolism of BCAAs to TCA intermediates in proliferating cells (22). We then explored whether excess KIC may be excreted by NSCLC tumors for further metabolism by other tissues such as liver, which has limited Bcat, but high Bckdh activity (21, 23).…”
Section: Main Textsupporting
confidence: 93%
“…S2, G–I). This is consistent with recent work demonstrating minimal catabolism of BCAAs to TCA intermediates in proliferating cells (22). We then explored whether excess KIC may be excreted by NSCLC tumors for further metabolism by other tissues such as liver, which has limited Bcat, but high Bckdh activity (21, 23).…”
Section: Main Textsupporting
confidence: 93%
“…10 Interestingly, quite recently, isotope studies in adipocytes demonstrated that BCAA catabolism improves adipocyte differentiation. 43 With decreased BCAA catabolism in obesity, SAT may fail to enlarge adequately, 43 which in turn may favour deposition of ectopic fat and subsequent effects on insulin sensitivity. 44 Thus, our study provides a mechanistic link (reduction in mitochondrial catabolism of BCAAs) for the association between circulating BCAA and the risk of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, AMA protein had the ability to maintain the CHO and TG at the same levels of Ctrl diets (Table 3) while SOY treatment produced a rise of CHO and TG levels and the only difference between the AMA and SOY protein isolates is their amino acid composition. Gorinstein et al [32] reported that SOY has a higher content of branched chain amino acids (BCAAs) such as leucine, isoleucine, and valine and recent reports have shown that BCAAs have an important role in adipocyte metabolism, which could impact in lipogenesis and adipose tissue accumulation, as well as in type 2 diabetes [33,34]. Moreover, it is well known that amaranth proteins contains a better balance of essential amino acids, especially amaranth globulins contains higher amount methionine than soybean proteins.…”
Section: Discussionmentioning
confidence: 99%